Effects of Genially Directed Reading Thinking Activities on College Students’ Motivation and Academic Performance in World Literature: A Literature Review - Marko Aratea; Lourdes Nati (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
World Literature instruction in higher education still continues in facing challenges characterized by low level of students' participation, the use of traditional lecture teaching method, and lack of development of higher-order interpretive skills like inference, literary analysis and critical reading. While there is a considerable body of evidence on the positive effects of gamification on students' motivation and performance in learning languages and skills, the research interest is largely focused on the language learning field and less on courses with a literature focus, where the learning process is more complex. In addition, gamification is often talked about generally without being clearly expressed with reference to platforms, structured instructional designs, or a connection to existing reading comprehension activities, such as Directed Reading Thinking Activities (DRTA). The literature review focuses on the current studies on gamified instruction, traditional literature teaching approaches, student motivation, academic achievement, pedagogies based on DRTA, and with special emphasis on the interactive learning environments created with Genially in tertiary education. The results reveal that, though gamification has a positive impact on learner engagement and motivation, its use in the interpretation of literary texts still has not received much attention. Similarly, the relationship between students' motivation and academic achievement in the context of structured gamified literature is not well demonstrated. The review outlines the requirement of a more systematic teaching through instructional model plan in World Literature teaching that combines the use of games and DRTA to enhance interpretive learning outcomes.